PENGARUH SEMANGAT KERJA, KEMAMPUAN KERJA DAN PEMBAGIAN KERJA TERHADAP PRESTASI KERJA (Studi Kasus pada Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Surakarta) - Sutanto, Djoko; Muhdiarto, Untung; Martomo, Yitno Puguh; Anggraeni, Astrid Silvia (Surakarta Management Journal, 2024)
This research examines the influence of work enthusiasm, work ability, and work division to work performance. The research object is the personnel of the Surakarta City Personnel and Human Resources Development Agency. There were 60 research participants and all of them were used as samples. Data collection techniques include surveys, documents, and literature reviews. Primary and secondary data are two types of data sources. The results of data analysis show that: (1) work enthusiasm has a positive and large influence on work performance; (2) work ability has a positive and significant effect on work performance; and (3) work division has a positive and significant effect on work performance. Work performance is influenced positively and significantly by work enthusiasm, work ability, and division of work. In relation to work performance, work enthusiasm is more influential than work ability and work division. 90.70% of work performance is influenced by work enthusiasm, work ability and work division. The other 9.30% is influenced by factors not included in this research, such as motivation, discipline, leadership, and so on.